Genetic predictors of relapse rate in pediatric MS - Graves, Jennifer S; Barcellos, Lisa F; Shao, Xiaorong; Noble, Janelle; Mowry, Ellen M; Quach, Hong; Belman, Anita; Casper, T Charles; Krupp, Lauren B; Waubant, Emmanuelle (Multiple sclerosis, 2016)
Genetic ancestry, sex, and individual alleles have been associated with multiple sclerosis (MS) susceptibility. To determine whether established risk factors for disease onset are associated with relapse rate in pediatric MS. Whole-genome genotyping was performed for 181 MS or high-risk clinically isolated syndrome patients from two pediatric MS centers. Relapses and disease-modifying therapies were recorded as part of continued follow-up. Participants were characterized for 25-hydroxyvitamin D serum status. Ancestral estimates (STRUCTURE v2.3.1), human leukocyte antigen (HLA)-DRB1*15 carrier status (direct sequencing), sex, and a genetic risk score (GRS) of 110 non-HLA susceptibility single-nucleotide polymorphisms (SNPs) were evaluated for association with relapse rate with Cox and negative binomial regression models. Over 622 patient-years, 408 relapses were captured. Girls had greater relapse rate than boys (incident rate ratio (IRR) = 1.40, 95% confidence interval (CI) = 1.04-1.87, p = 0.026). Participants were genetically diverse; ~40% (N = 75) had <50% European ancestry. HLA-DRB1*15 status modified the association of vitamin D status (p = 0.022) with relapse rate (per 10 ng/mL, in DRB1*15+ hazard ratio (HR) = 0.72, 95% CI = 0.58-0.88, p = 0.002; in DRB1*15- HR = 0.96, 95% CI = 0.83-1.12, p = 0.64). Neither European ancestry nor GRS was associated with relapse rate. We demonstrate that HLA-DRB1*15 modifies the association of vitamin D status with relapse rate. Our findings emphasize the need to pursue disease-modifying effects of MS genes in the context of environmental factors.